Maglehøj – preservation of birch bark in a passage grave with evidence of forced entry in prehistory - Dehn, Torben; Larsen, Poul Klenz (Danish Journal of Archaeology, 2023)
Maglehøj is a Danish passage grave which has birch bark incorporated into its construction. An account of the opening of the monument in 1823 reports the discovery of an earth-free chamber and describes constructional details, including the use of birch bark. An investigation undertaken in 1997, prompted by the information given in this account, revealed that the birch bark was relatively well preserved and that there had been a break-in through one gable of the chamber later in prehistory. This article gives several examples of similar intrusions, which were a more common phenomenon than previously appreciated. The results of a 12-month investigation of the climatic conditions inside Maglehøj’s chamber, aimed at optimising preservation of the birch bark, are also presented. The investigation included measurements of air change and humidity carried out under different conditions. The outcome was a recommendation that the entrance to the chamber be closed with an air-tight seal.